Long Non-coding RNA MEG3 Induces Renal Cell Carcinoma Cells Apoptosis by Activating the Mitochondrial Pathway - Wang, Miao; Huang, Tao; Luo, Gang; Huang, Chao; Xiao, Xing-yuan; Wang, Liang; Jiang, Guo-song; Zeng, Fu-qing (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
Summary： This study aimed to examine the effect of long non-coding RNA （LncRNA） MEG3 on the biological behaviors of renal cell carcinoma （RCC） cells 786-0 and the possible mechanism. MEG3 expression levels were detected by RT-qPCR in Rmaor tissues and adjacent non-tumor tissues from 29 RCC patients and in RCC lines 786-0 and SN12 and human embryonic kidney cell line 293T. Plasmids GV144-MEG3 （MEG3 overexpression plasmid） and GV144 （control plasmid） were stably transfected into 786-0 cells by using lipofectamine 2000. Cell viabilities were determined by MTT, cell apoptosis rates by flow cytometry following PE Annexin V and 7AAD staining, apoptosis-related protein expressions by Western blotting, and Bcl-2 mRNA by RT-qPCR in the transfected cells. The results showed that MEG3 was evidently downregulated in RCC tissues （P〈0.05） and RCC cell lines （P〈0.05）. The viabilities of 786-0 cells were decreased significantly after transfection with GV144-MEG3 for over 24 h （P〈0.05）. Consistently, the apoptosis rate was significantly increased in 786-0 cells transfected with GV144-MEG3 for 48 h （P〈0.05）. Furthermore, overexpression of MEG3 could reduce the expression of Bcl-2 and procaspase-9 proteins, enhance the expression of cleaved caspase-9 protein, and promote the release of cytochrome c protein to cytoplasm （P〈0.05）. Additionally, Bcl-2 mRNA level was declined by MEG3 overexpression （P〈0.05）. It was concluded that MEG3 induces the apoptosis of RCC cells possibly by activating the mitochondrial pathway.